The Proper Location of Verifying Affidavit, Effects and Reasons in Matrimonial Proceedings in Nigeria - Ituma, Chibueze Calistus (ABUAD Private and Business Law Journal, 2018)
The Location of verifying affidavit in a petition for a decree of dissolution of marriage or answer thereof has become a booby trap for many lawyers and judges of trial courts. Verifying Affidavit is the heart and soul of a petition, indeed, a mandatory requirement for every divorce petition or answer. The dislocation of verifying affidavit in defiance of the obligatory injunction of Order V Rule 10 (1) of the Matrimonial Causes Rules of 1983 always attracts severe sanction of outright dismissal of the Petition. The consequence is perpetual multiple preliminary objections, appeals to superior courts and dismissal of petitions, leaving the petitioners in a state of drudgery and marital comatose, since an attempt to remarry without first dissolving a statutory marriage amounts to bigamy. The purpose of this article is to render an accurate interpretation of Order V Rule 10 (1) of the Matrimonial Causes Rules and save legal practitioners the agony of having their petitions dismissed on account of improper placement of verifying affidavit. The article is structured into five segments namely: Introduction, interpretation of Order V Rule 10 (1) of Matrimonial Causes Rules, Case Law analysis of the issue, sample of a petition with verifying affidavit and conclusion. Doctrinal research methodology was applied in arriving at a valid conclusion. Emphases were placed on statutes and case laws as primary sources. Reliance was as well placed on journal articles, textbooks. Internet materials, among others, as secondary sources.